If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3x = 7x + 5 Reorder the terms: 15 + -3x = 5 + 7x Solving 15 + -3x = 5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 15 + -3x + -7x = 5 + 7x + -7x Combine like terms: -3x + -7x = -10x 15 + -10x = 5 + 7x + -7x Combine like terms: 7x + -7x = 0 15 + -10x = 5 + 0 15 + -10x = 5 Add '-15' to each side of the equation. 15 + -15 + -10x = 5 + -15 Combine like terms: 15 + -15 = 0 0 + -10x = 5 + -15 -10x = 5 + -15 Combine like terms: 5 + -15 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 6cos-1=2 | | 4(q)=52 | | 2(4x+1)=3x-9x | | 1996.43x=7385-67x | | R-(-5)=9 | | 8(4-n)+2=90 | | 44221=a*2+b | | 2(5x+7)+3=10x+17 | | 2x-17=2x-12 | | 3(r+7)=15 | | 4r-1=-4+4r+3 | | -4(x+9)=7-3x | | 2(4x-10)=46 | | 3m+3=5 | | -15+3=-2(x+7) | | 1996+43x=3716 | | 3x+3=(x+3) | | 10(a-2)=-70 | | -86=-7n+4(-n-5) | | 7-3x-5-3x=5 | | Kx-3x=-2+5k | | 360-76= | | -8-14v=314 | | 5(-x-3)=5 | | 16x+34x+24x=370 | | 9(n+12)=144 | | 180-76= | | -3(x-7)=2(3x-5) | | 28=2+2a | | 2(x-8)-5(x+6)=2 | | -3x+21=6x-10 | | 4a-3b+2c= |